Evaluation of Digital Panoramic Imaging for Incidental Findings in Completely Edentulous Patients in a Libyan Subpopulation (LIMU Dental Center) - Mervet El-Zuki,; ALQUTANI, AYAD; Mahmoud Alqutani,; Adyan Saad, (AlQalam Journal of Medical and Applied Sciences, 2025)
Reduction in the rate of tooth loss and the need for complete dentures has a powerful effect on dental education and treatment modalities. Data regarding the levels of tooth loss and prosthetic treatment patterns of the population for all countries must be obtained, and the changes that occur over time need to be determined. The prevalence of complete edentulism varies from country to country and from one region to another. According to the current English literature, there is no available data for Libya in this regard. This study was conducted to evaluate the prevalence of complete edentulism retrospectively and to evaluate the frequency and location of significant incidental findings concerning age, gender, type of arch (maxilla/mandible), on digital panoramic images of edentulous patients attending the Clinical Dental Center in the Faculty of Dentistry at the Libyan International Medical University (LIMU), Benghazi- Libya. It is a cross-sectional, retrospective study; digital panoramic images of patients attending the Clinical Dental Center at LIMU from April 2021 to February 2023 will be retrieved and evaluated. The prevalence of complete edentulism will be determined among 1553 digital panoramic radiographs (original sample), which will be subjected first to inclusion and exclusion criteria. Radiographic incidental findings are identified as: impacted teeth, retained roots, radiopaque and radiolucent areas, atrophic crest, foreign bodies, styloid process elongation, soft tissue calcification, maxillary sinus findings, and any other findings specific to this Libyan subpopulation. A total of 1553 panoramic images were analyzed in this study, out of which 126 (8.1%) were completely edentulous, and out of these 83 (65.8%) were associated with positive incidental findings, as of the images belonged to 82 (65.1%) males and 44 (34.9%) belonged to females, and atrophic maxilla being the most frequently observed finding 51 (35.7%), atrophic mandible found in 31 (21.7%) and styloid ligament calcification presented in 24 (16.8%) of total completely edentulous panoramic images. The result of this study showed that the rate of positive incidental findings detected in digital panoramic images of completely edentulous patients was high. Accordingly, taking panoramic images of completely edentulous patients before prosthetic replacement is important to avoid dental and medical conditions that could affect these patients.